Design of a Digitally Controlled Tunable Matching Network Based on GaN FETs - Kawin Surakitbovorn; Juan Rivas-Davila (My University, 2025)
Radio frequency (RF) power amplifiers are integral to many academic, medical, and industrial applications. In many of these applications, dynamic impedance matching is a critical requirement. While conventional tunable matching networks (TMNs) with motor-controlled variable inductors/capacitors provide excellent matching range, their response times are inadequate for applications with rapid load changes. This paper presents a design of digitally controlled TMNs suitable for quick impedance matching at high frequencies (10s of MHz) and high power levels (100s of Watts). Our proposed matching system employs a secondary high-speed TMN based on wide bandgap GaN field effect transistors configured as digitally controlled variable capacitors in a double Pi network. The prototype system, tested at 13.56 MHz and 500 W, achieves impedance matching for loads with reflection coefficients up to 0.5 at any angle with less than 1% reflected power. Unlike techniques requiring device switching at RF frequency, our approach offers a simpler implementation while maintaining high power handling capability.
Keywords: Advanced Power Amplifier Design; GaN-based semiconductor devices and materials; Radio Frequency Integrated Circuit Design